A ciência de Hume e o problema do mundo externo - Alves, Marcelo de Sousa Ferreira (2023)
The main objective of this research is to understand Hume's theory of knowledge as a relationship between science (experimental method) and philosophy (problem of the external world), that is, to think of his philosophical project as a mix between science and philosophy. This will make it possible to raise some problems with the dynamics between these two parties, where one leads to dependence on the other. To this end, the research is divided into three parts. The first chapter, entitled “Hume's Ambition: the construction of a science of man and the path that leads to it” aims to seek Hume's science project in the modern scientific and philosophical tradition. In this way, we will briefly expose the paths and processes that led to the birth of modern science through the scientific revolution, passing through scientists and philosophers such as Galileo, Descartes, Newton, Locke and Berkeley, until arriving at Hume. This chapter is important because it sets the stage for Hume's scientific and philosophical claims. The second chapter, entitled “From Mental Geography to the Science of Human Nature”, we will see the formulation, properly speaking, of Hume's science, together with its object of study or investigation, that is, man and natural beliefs. This chapter will also address the problem of induction, as well as the difficulties inherent in a radial skeptical interpretation of Hume's philosophy. The third and final chapter, entitled “The Science of Man and the Fiction of the World” aims to point to some fundamental problems that arise in causal scientific investigation when we consider the subsequent investigation of belief in the external world, and which is only from from this investigation that the principle of human nature can be understood as a true principle.